Upgrading Properties and Circularity of the Recycled Flexible Polypropylene by Developing Composites with an Optimal Combination of a Fumed Silica and Maleated Polypropylene Copolymer: Influence of the Addition of Copolymer, Type of Fumed Silica and the Silica/Copolymer Ratio on Packaging Properties - Guarda-Moraga, A; Galotto-Lopez, M; Velasquez, E (Elsevier Ltd, 2024)
Rigid polypropylene is mechanically recycled but flexible polypropylene is mostly used in energetic valorization because of the poor properties of the recycled polymer. A recycled polypropylene-based composite with outstanding properties for flexible food packaging was developed. For the first time, the influence of maleated polypropylene copolymer addition and the fumed silica/copolymer ratio on the packaging properties of recycled flexible polypropylene under the effects of silica hydrophilicity was investigated. The structural, morphological, thermal, mechanical, melt flow, overall migration, water vapor barrier and sealing properties of the developed nanocomposites were analyzed. Prominently, the addition of 1:1 maleated polypropylene and hydrophobic nanosilica improved the global performance of all tested methods. The recycled polypropylene had an overall migration to olive oil of 17 mg dm−2, exceeding the limit allowed for food packaging, but the developed added-value composite reduced it to the tolerance limit according EU legislation. The seal strength was drastically increased by 50 % with adhesive peeling, high thermal stability, and well-dispersed particles without affecting the ductility. © 2024 The Authors